3D electrical structure and crustal deformation of the Lajishan Tectonic Belt, Northeastern margin of the Tibetan Plateau. (February 2022) - Zhao, Lingqiang; Zhan, Yan; Wang, Qingliang; Sun, Xiangyu; Hao, Ming; Zhu, Yiqing; Han, Jing
Graphical abstract: Highlights: A steep high-conductivity layer exists in the middle–lower crust to the south of the belt. The high-resistivity body on the northern side may have blocked the high-conductivity layer, which formed the positive flower structure of the Lajishan tectonic belt and resulted in intense orogenic and seismic activities. Crustal shortening may dominate the tectonic deformation of the NE Tibetan Plateau. Abstract: The Lajishan tectonic belt is the most recently active orogenic belt in the northeastern Tibetan Plateau and represents a topographical boundary between the high Tibetan Plateau and the low-lying Longzhong basin to the east. Imaging the crustal structure beneath the Lajishan tectonic belt can improve our understanding about the regional tectonic deformation pattern, mechanisms of the outward growth of the Tibetan Plateau, and seismogenic environment in this area. In this study, we conducted two magnetotelluric (MT) profile measurements across the Lajishan tectonic belt in each section. Based on our newly-collected MT data and previous dataset in this area, a three-dimensional (3D) image of the deep electrical structure of the Lajishan tectonic belt is obtained by using 3D MT inversion and imaging technologies. Furthermore, by including 3D crustal deformation field information, a tectonic deformation model of the Lajishan tectonic belt and its adjacent area was constructed. Our present results show that a steep high-conductivity layer developed beneath the Lajishan tectonic belt and the adjacent Jianzha–Xunhua Basin and West Qinling Block, which then connected with a horizontal high-conductive layer underneath the Tibetan Plateau. Findings suggest that the Lajishan tectonic belt acts as a physical property boundary zone separating a high-resistivity body to the north from a deep high-conductivity layer in the middle-lower crust to the south. The high-conductivity layer, with a shallower depth from southwest to northeast, may be related to the NE-trending compression of the northeastern Tibetan Plateau, which was blocked by the high-resistivity body underneath the Xining basin. This led to the formation of a positive flower structure in the Lajishan tectonic belt, resulting in intense orogenic and seismic activities. The south-dipping Northern Lajishan Fault is the main boundary fault of the Lajishan tectonic belt and plays an important role in the mountain formation process, as suggested by asymmetry surface topography. The absence of a large-scale NE-SW-trending continuous high-conductivity layer in middle-lower crust indicates that the tectonic deformation of the northeastern Tibetan Plateau is dominated by a continuous upper-crustal compressing and shortening, instead of the lower-crustal flow.